2012
DOI: 10.1530/eje-12-0746
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of etomidate use in the management of hypercortisolaemia

Abstract: We appreciate the letter from of Dr Soh et al. regarding our review on the use of etomidate in the treatment of Cushing's syndrome. We note that in their experience, our recommended dose regimen of 2.5 mg/h or thereabouts appears to be a safe and effective starting dose in most patients, and we note the utility and ease of use of the lipid formulation and its relative freedom from side effects compared with the more commonly used propylene glycol formulation; these are very helpful comments. Their experience i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…10,88 This has led some to recommend that etomidate only be administered to treat CS in an ICU setting. 10,14,15 Non-sedating etomidate analogs In order to avoid the sedative-hypnotic action of etomidate, etomidate analogs (e.g. dimethoxyetomidate) have recently been developed which retain the potent and efficacious adrenocortical suppressive actions of etomidate but lack its potentiating effect on GABA A Rs and thus its ability to produce sedation or hypnosis.…”
Section: Adrenocortical Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…10,88 This has led some to recommend that etomidate only be administered to treat CS in an ICU setting. 10,14,15 Non-sedating etomidate analogs In order to avoid the sedative-hypnotic action of etomidate, etomidate analogs (e.g. dimethoxyetomidate) have recently been developed which retain the potent and efficacious adrenocortical suppressive actions of etomidate but lack its potentiating effect on GABA A Rs and thus its ability to produce sedation or hypnosis.…”
Section: Adrenocortical Insufficiencymentioning
confidence: 99%
“…Etomidate also has certain features that may be advantageous for the acute management of severe CS, including a rapid onset of action and the ability to administer parenterally. [7][8][9][10][11][12][13] However, etomidate's high efficacy in treating CS is generally thought to require administering doses which risk producing sedation and hypnosis. 10,14,15 To overcome this limitation, efforts are being made to optimize etomidate dosing to allow reductions in cortisol levels without producing sedation or hypnosis and to develop etomidate analogs that retain the ability to inhibit cortisol production but lack sedative-hypnotic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies demonstrated that inhibition of cortisol was rapidly achieved with low-dose (2.5 mg/h) etomidate in patients with hypercortisolism and was distinct from the sedative effects of the drug [33]. In patients with CS, etomidate treatment resulted in significant suppression of serum cortisol levels within 11 h of infusion [34].…”
Section: Adrenal Steroidogenesis Inhibitors Currently In Clinical Usementioning
confidence: 99%
“…In an emergency setting, patients with CS who received etomidate at a dose of 0.1 mg/kg per hour exhibited rapid and prolonged suppression of serum cortisol levels [34]. The most common side effects associated with etomidate were hypnotic effect, reduced blood pressure, myoclonus, dystonia, nausea, and vomiting [31, 33]. Adrenal insufficiency has also been reported, which may require glucocorticoid replacement [31], thus a block-and-replace protocol is used in most cases.…”
Section: Adrenal Steroidogenesis Inhibitors Currently In Clinical Usementioning
confidence: 99%
See 1 more Smart Citation